PERAN PERWAKILAN DIPLOMATIK DALAM PERLINDUNGAN PEKERJA MIGRAN INDONESIA DI MALAYSIA PASCA DITANDATANGANINYA MOU TENTANG ONE CHANNEL SYSTEM - Fitria, Yenni (Ensiklopedia of Journal, 2025)
Abstract: Resolving conflicts between countries will rely on one of the national laws of a country in conflict, it feels unfair because the values that are embedded in each individual are definitely different. Protection is not only in the form of legal protection but also providing outreach and providing foreign language learning facilities. The protection referred to in the article above can be carried out by diplomatic representatives who are "The conduct by government officials of negotiations and other relations between nations; the art of science of conducting such negotiations; skill in managing negotiations, handling of people so that there is little or no ill-will act." From this definition, it can be seen that actions by government officials regarding negotiations and other relations between countries, knowledge about negotiations, skills in managing negotiations, handling individuals so that no bad actions are taken, all of this can be interpreted as diplomacy. Diplomatic representatives are really needed as representatives of countries with the duties and functions of carrying out cooperation between countries in maintaining world peace for the welfare of humanity based on freedom and social justice.Keywords: Diplomatic Representatives, Migrant Workers, Malaysia.